Role of imaging in surgical decision making in young knee osteoarthrosis - Malini Lawande; Aditya Daftary; Ankita Ahuja; Bhushan Sabnis (European Journal of Radiology Open, 2022)
Osteoarthrosis is the most common form of knee arthritis, characterized by pain and discomfort from primarily articular cartilage wear. Traditionally in its end stage, it has been treated with total knee arthroplasty, a permanent process with a life span of ten to fifteen years and challenges with revision. With an increasing longevity and epidemic of obesity that the population is facing, naturally, we are seeing more and more patients with osteoarthrosis at a younger age. This makes it imperative to extend the life of the native knee by conservative measures, injections of steroid, hyaluronic acid, or biologicals and finally a slew of surgical alternatives ranging from joint realignment to partial and total joint replacement. Besides the clinical presentation, decisions are made based on joint alignment, extent and degree of cartilage wear and the status of the subchondral bone. Imaging plays an invaluable role in surgical decision making. In this article, we will discuss how imaging is used in our practice during decision making for the management of the young osteoarthritic knee.